2009
DOI: 10.1136/bjo.2008.149195
|View full text |Cite
|
Sign up to set email alerts
|

Macular hole formation after macular haemorrhage associated with rupture of retinal arterial macroaneurysm

Abstract: These results suggest that the presence of subretinal and sub-ILM haemorrhages after rupture of a retinal arterial macroaneurysm may contribute to formation of an MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…The onset of a macular hole (MH) after the rupture of a retinal arterial macroaneurysm (RAMA) is a sight-threatening complication of RAMA [ 1 , 2 , 3 ]. Previous reports have suggested that MH can develop in 5.9–12.5% of RAMA ruptures, and that the postoperative primary anatomic success rate of surgical intervention for MH secondary to RAMA is between 57.1 and 75.0% [ 4 , 5 ], which is lower than that of surgical intervention for idiopathic MH [ 6 , 7 ]. Moreover, there is limited information with respect to the most effective surgical procedure for MH after RAMA rupture.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of a macular hole (MH) after the rupture of a retinal arterial macroaneurysm (RAMA) is a sight-threatening complication of RAMA [ 1 , 2 , 3 ]. Previous reports have suggested that MH can develop in 5.9–12.5% of RAMA ruptures, and that the postoperative primary anatomic success rate of surgical intervention for MH secondary to RAMA is between 57.1 and 75.0% [ 4 , 5 ], which is lower than that of surgical intervention for idiopathic MH [ 6 , 7 ]. Moreover, there is limited information with respect to the most effective surgical procedure for MH after RAMA rupture.…”
Section: Introductionmentioning
confidence: 99%
“…These MHs are distinct from conventional MHs that evolve slowly through vitreoretinal traction. Their causative mechanisms are multiple and a matter of discussion,30 31 but acute pulsion from behind through a subretinal or intraretinal bleeding in combination with retinotoxicity of blood are probably important contributors 32 33. Incidences of MH formation after RAMA rupture were 5–12% in the literature30 31 and 6% (3/49) in our series.…”
Section: Discussionmentioning
confidence: 54%
“…Several macular pathologies have been reported that may develop secondary MH such as cystoid macular edema, subretinal fluid due to rhegmatogenous retinal detachment, and SMH [2][3][4][5][6][7][8][9][10]. In most of the secondary MH associated with SMH, the SMH was caused by rupture of a retinal arterial macroaneurysm (RAM) [17][18][19]. There are several reports of secondary MH associated with choroidal neovascularization, but they developed after absorption of submacular fluid, not SMH [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In a case of SMH due to RAM, it was considered that secondary MH was caused by rapid increase in intraretinal pressure (early onset) or by retinal degeneration (late onset) [18]. Sagara et al reported that the presence of subretinal and sub-internal limiting membrane (ILM) hemorrhages after rupture of a RAM might contribute to formation of an MH [17].…”
Section: Discussionmentioning
confidence: 99%